Netradio for UM (Back-end framework) / Razmah Mahad - Razmah, Mahad (2005)
This graduation project report was a partial requirement of the Bachelor Degree of Computer Science. This project focused on the testing and implementation of streaming. Streaming multimedia files using multicast and unicast technology through LAN with conserving network resources. It is also an effort being carried out to provide a multimedia and interactive Web-based system for Faculty of Computer Science and Information Technology. Multimedia has become a popular catchword during the last few years. The idea behind a multimedia network is a single network combining an improving all current technologies that realizes fast and convenient access for the customer to voice and data applications. The NetRadio concept is first conceived to solve the weakness of traditional radio in this demanding social. The NetRadio is designed to be a multimedia environment, utilizing state-of-the-art currently powerful technology to accommodate user requirement. Since the study of multimedia broadcasting is still a new topic in computer world, only limited streaming technology available for this project. The core technology deployed in this project is Microsoft Windows Media Services, which is a powerful streaming technology use for stream all on-demand Radio programs to users. Finally, it concludes that NetRadio can be implemented using either unicast or multicast stream and all streams will be able to provide the optimum quality if implemented in Local Area Network.